2007
DOI: 10.1158/1535-7163.mct-06-0342
|View full text |Cite
|
Sign up to set email alerts
|

A phase I trial of hyperthermia-induced interleukin-12 gene therapy in spontaneously arising feline soft tissue sarcomas

Abstract: Interleukin-12 (IL-12), a proinflammatory cytokine, shows anticancer properties. Systemically administered IL-12 causes dose-dependent toxicity. To achieve localized intratumoral gene expression, an adenoviral gene therapy vector with IL-12 controlled by a heat-inducible promoter (heat shock promoter 70B) was developed and tested in a phase I clinical trial in cats with spontaneously arising soft tissue sarcoma. A feasibility study was done in 16 cats with soft tissue sarcoma using murine IL-12 and/or enhanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 56 publications
1
28
0
1
Order By: Relevance
“…The delivery systems for IL-12 gene therapy are various and include transfer of naked plasmid DNA alone [27,28], adenoviral [29][30][31][32][33] or other viral vectors [34][35][36], as well as gene gun [37,38], electroporation [39][40][41][42] and other non-viral vectors [43,44]. Clinical studies in human and also in veterinary oncology were initiated and the first results showed that IL-12 gene therapy is a safe treatment with some beneficial clinical effect [28,[45][46][47][48][49][50][51][52][53][54][55].…”
Section: Introductionmentioning
confidence: 99%
“…The delivery systems for IL-12 gene therapy are various and include transfer of naked plasmid DNA alone [27,28], adenoviral [29][30][31][32][33] or other viral vectors [34][35][36], as well as gene gun [37,38], electroporation [39][40][41][42] and other non-viral vectors [43,44]. Clinical studies in human and also in veterinary oncology were initiated and the first results showed that IL-12 gene therapy is a safe treatment with some beneficial clinical effect [28,[45][46][47][48][49][50][51][52][53][54][55].…”
Section: Introductionmentioning
confidence: 99%
“…With the advances in the field of gene therapy, this new therapeutic tool is steadily gaining its acceptance also in clinical veterinary medicine. In the last decade, a number of gene therapy clinical trials have been conducted on companion animals, employing both viral and nonviral vectors and evaluating its effects primarily in oncologic, haematologic, musculoskeletal and cardiovascular diseases (Bergmann et al, 2003;Bodles-Brakhop et al, 2008;Dow et al, 2005;Draghia-Akli et al 2002;Herzog et al, 2001;Huttinger et al, 2008;Jahnke et al, 2007;Kamstock et al, 2006;Kornegay et al, 2010;Ohshima et al, 2009;Pavlin et al, 2011;Siddiqui et al, 2007;Sleeper et al, 2010;Z. Wang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Viral delivery was instituted using adenoviral vectors, which were delivered primarily intratumorally, for example into different types of fibrosarcoma [4][5][6] and Ewing's sarcoma. 7 Adenoviral constructs expressing IL-12 were also delivered intranasally for treatment of osteosarcoma lung metastases.…”
Section: Introductionmentioning
confidence: 99%